Developing a resilience design framework for disaster evacuation centres/ Aainaa Suhardi - Suhardi, Aainaa (2022)
Due to the challenges of disasters in Malaysia, local residents and relief teams are given early warning and time to mitigate and prepare for evacuation in advance. Disaster victims will be carefully assisted to the designated public buildings for shelter, safety, and protection. However, the existing spaces and facilities of these buildings are mainly designed for their specific purposes. The inefficiency of spaces and facilities was recognised as a major issue. Therefore, the buildings' resilience is questionable. Thus, the Multidisciplinary Centre for Earthquake Engineering Research's 4R resilience framework study is considered practical for the centre's resilience investigation. It combines robustness, redundancy, resourcefulness, and rapidity to build a more disaster-resilient centre. The research employs a multistage investigation that combines qualitative and quantitative methods. Firstly, document analyses of official shelter guidelines; secondly, a case study of selected disaster evacuation centres; thirdly, semi-structured interviews; and finally, a questionnaire survey for field testing. The main findings of the research are the minimum design standards, the space provisions of the centre and the integration of resilience properties into the design and space.